{jatex}\large \frac {x^3+x^2-4x-4}{x^3+6x^2+5x-12}>0{/jatex}

{jatex}\large \frac {x^2(x+1)-4(x+1)}{x^3-x^2+7x^2-7x+12x-12} >0{/jatex}

{jatex}\large \frac {(x+1) \left( x^2 -4 \right) }{x^2(x-1)+7x(x-1)+12(x-1)} >0{/jatex}

{jatex}\large \frac {(x+1)(x-2)(x+2)}{(x-1)\left(x^2+7x+12 \right)} >0{/jatex}

Վերլուծենք արտադրիչների

{jatex}x^2+7x+12{/jatex}

{jatex}x^2+7x+12=0{/jatex}

{jatex}D=7^2-4 \cdot 12=1{/jatex}

{jatex}\large x_1= \frac {-7-1}{2}=-4 \quad x_2 = \frac {-7+1}{2} = -3{/jatex}

Ըստ Վիետի թեորեմի

{jatex}x^2+7x+12=(x+3)(x+4){/jatex}

Տեղադրենք

{jatex}\large \frac {(x+1)(x-2)(x+2)}{(x-1)(x+3)(x+4)} >0{/jatex}

{jatex}x \in ( - \infty ; -4) \cup (-3;-2) \cup (-1; 1) \cup ( 2 ; + \infty ){/jatex}

Պատ․՝ {jatex}( - \infty ; -4) \cup (-3;-2) \cup (-1; 1) \cup ( 2 ; + \infty ){/jatex}։

No thoughts on “Լուծել անհավասարումը”

 

Ուղարկել էջը